-(3y+4)-(-2y+2)=3

Simple and best practice solution for -(3y+4)-(-2y+2)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(3y+4)-(-2y+2)=3 equation:


Simplifying
-1(3y + 4) + -1(-2y + 2) = 3

Reorder the terms:
-1(4 + 3y) + -1(-2y + 2) = 3
(4 * -1 + 3y * -1) + -1(-2y + 2) = 3
(-4 + -3y) + -1(-2y + 2) = 3

Reorder the terms:
-4 + -3y + -1(2 + -2y) = 3
-4 + -3y + (2 * -1 + -2y * -1) = 3
-4 + -3y + (-2 + 2y) = 3

Reorder the terms:
-4 + -2 + -3y + 2y = 3

Combine like terms: -4 + -2 = -6
-6 + -3y + 2y = 3

Combine like terms: -3y + 2y = -1y
-6 + -1y = 3

Solving
-6 + -1y = 3

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -1y = 3 + 6

Combine like terms: -6 + 6 = 0
0 + -1y = 3 + 6
-1y = 3 + 6

Combine like terms: 3 + 6 = 9
-1y = 9

Divide each side by '-1'.
y = -9

Simplifying
y = -9

See similar equations:

| 3(6)-3x=9 | | 2p^2-7pq+6q^2=0 | | 3(2z-5)=5(z+4) | | 3m^2+11mn+6n^2=0 | | 0.45(60)+0.6x=0.5(60+x) | | 3x-5(x-3)=-9+2x-8 | | 4y^2=20y | | 0.45(60)+0.6x=0.55(60+x) | | 7-12s-4s^2=0 | | 8x-12=2x^2 | | x^2-15x-2=0 | | 1-5b-8b^2=0 | | 4x^2+y^2-8x+4y+4=0 | | X(x-3)=x+3 | | 9+6k-8k^2=0 | | 5+7x-6x^2=0 | | 2x^2+7x+14=0 | | 6a^2-5a-2=0 | | 2x^2+7+14=0 | | 6a^2-51-2=0 | | r^2-8r=0 | | 4y^2-y-3=0 | | (2x^3*-7)(6x^3-6)=0 | | 8m^3n^4-22m^5n^6= | | -7x^2-66x-27=0 | | (x-5)(x+1)=4 | | 2+5*x=4x | | 3r^2-2r-5=0 | | -6y-5=7+9y | | 3r^2-24-5=0 | | 10r+8=58 | | 72m^7n+24n= |

Equations solver categories